Coronary CT angiography: First comparison of model-based and hybrid iterative reconstruction with the reference standard invasive catheter angiography for CAD-RADS reporting - Aiste Matuleviciute-Stojanoska; Julia Sautier; Verena Bauer; Martin Nuessel; Volha Nizhnikava; Christian Stumpf; Thorsten Klink (European Journal of Radiology Open)
Background: The purpose of this study was to compare CCTA images generated using HIR and IMR algorithm with the reference standard ICA, and to determine to what extend further improvements of IMR over HIR can be expected. Methods: This retrospective study included 60 patients with low to intermediate CAD risk, who underwent coronary CTA (with HIR and IMR) and ICA. ICA was used as reference standard. Two independent and blinded readers evaluated 2226 segments, classifying stenosis with CAD-RADS (significant stenosis ≥3). Image quality was assessed with a 5-point scale, SNR in the ascending aorta, and FWHM of proximal LCA calibers. The impact of image noise, radiation dose, and BMI on diagnostic accuracy was evaluated using ROC curves and Fisher’s Exact Test. Quantitative plaque analysis was performed on 28 plaques. Results: IMR showed higher image quality than HIR (IMR 4.4, HIR 3.97, p<0.001) with better SNR (21.4 vs. 13.28, p<0.001) and FWHM (4.44 vs. 4.55, p=0.003). IMR had better diagnostic accuracy (ROC AUC 0.967 vs. 0.948, p=0.16, performed better at higher radiation doses (p=0.02) and showed a larger minimum lumen area (p=0.022 and p=0.046). Conclusion: IMR offers significantly superior image quality of CCTA, more precise measurements, and a stronger positive correlation with ICA. The overall diagnostic accuracy may be superior with IMR, although the differences were not statistically significant. However, in patients who are exposed to higher radiation doses during CCTA due to their constitution, IMR enables significantly better diagnostic accuracy than HIR thus providing a specific benefit for obese patients.